2010
DOI: 10.1177/1745691610369468
|View full text |Cite
|
Sign up to set email alerts
|

A New Social-Cognitive Developmental Perspective on Prejudice

Abstract: We argue that prejudice should be investigated in the context of social-cognitive development and the interplay between morality and group identity. Our new perspective examines how children consider group identity (and group norms) along with their developing moral beliefs about fairness and justice. This is achieved by developing an integrated framework drawing on developmental and social psychological theories of prejudice. This synthesis results in a perspective that provides a more contextualized analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
366
2
11

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 363 publications
(401 citation statements)
references
References 70 publications
22
366
2
11
Order By: Relevance
“…Each of these waveforms serves as a proxy for domain-general mechanisms of controlled and automatic processing in the developing brain. Moral sensitivity, in later development, is actually a careful integration of both an early automatic emotional component and a later cognitive reappraisal of stimuli, which can be explored in the temporal mechanical investigations of neural processing (1,39). By combining EEG with eye-tracking, behavioral measures, and parental and children's dispositions, the present study investigated the mechanisms at play during third-party social evaluations of prosocial and antisocial behaviors and their developmental trajectories.…”
Section: Significancementioning
confidence: 99%
“…Each of these waveforms serves as a proxy for domain-general mechanisms of controlled and automatic processing in the developing brain. Moral sensitivity, in later development, is actually a careful integration of both an early automatic emotional component and a later cognitive reappraisal of stimuli, which can be explored in the temporal mechanical investigations of neural processing (1,39). By combining EEG with eye-tracking, behavioral measures, and parental and children's dispositions, the present study investigated the mechanisms at play during third-party social evaluations of prosocial and antisocial behaviors and their developmental trajectories.…”
Section: Significancementioning
confidence: 99%
“…As previous research has noted, there is an age effect on prejudice, but the ages that apply to this dataset (∼13-17 years) have been found to be a stabilizing time for adolescent's attitudes (Raabe and Beelmann 2011). It is suggested that this is due to the increased importance of micro contextual influences in this age group (Rutland, Killen, and Abrams 2010).…”
Section: Time Mattersmentioning
confidence: 82%
“…24 As and Esch (2012,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39); Roediger (1991, 21, 57-59); Von Vacano (2012, 12). Additionally, psychological literature on the issue of prejudice seems to indicate that one's prejudices are created or motivated by the agent's beliefs about what kinds of traits are possessed by the subjects of their ire (Kunda and Thagard, 1996;Yamauchi, 2005 Rutland, Killen, andAbrams, 2010). Insofar as prejudices are relevant to disparate treatment, we can say that discrimination is motivated by one's beliefs about the traits that the victim possesses.…”
Section: Overlooked Similaritiesmentioning
confidence: 99%